In vivo and in vitro characterization of virulence-deficient mutants of Vibrio cholerae. - Baselski, V S (1979)
In vitro and in vivo interactions between Vibrio cholerae and the infant mouse intestinal environment were examined by using a number of virulence-deficient mutants of strain CA401 which are unable to induce a typical diarrheal response. In vitro interactions with upper bowel sections were evaluated by determining percent association of radiolabeled organisms with sections. In vivo behavior was evaluated in the upper bowel early in infection with radiolabeled inocula. Ths relative degree of mechanical clearance was indicated by the percent recovery of input label. The relative degree of multiplication and killing was determined by changes in the specific activities (counts per minute per colony-forming unit) of inocula compared with recovered viable organisms. The results indicated that, whereas some virulence-deficient mutant classes exhibit net multiplication in the upper bowel, other classes show net killing in and accelerated clearance from the upper bowel. The in vitro association patterns failed to correlate with in vivo upper bowel recovery.